Detection of Cryptosporidium and Cyclospora Oocysts from Environmental Water for Drinking and Recreational Activities in Sarawak, Malaysia - Lesley Maurice, Bilung; Ahmad Syatir, Tahar; Nur Emyliana, Yunos; Kasing, Apun; Lim, Yvonne Ai-Lian; Elexson, Nillian; Hashimatul Fatma, Hashim (Hindawi Publishing, 2017)
Cryptosporidiosis and cyclosporiasis are caused by waterborne coccidian protozoan parasites of the genera Cryptosporidium and Cyclospora, respectively. This study was conducted to detect Cryptosporidium and Cyclospora oocysts from environmental water abstracted by drinking water treatment plants and recreational activities in Sarawak, Malaysia. Water samples (12 each) were collected from Sungai Sarawak Kanan in Bau and Sungai Sarawak Kiri in Batu Kitang, respectively. In addition, 6 water samples each were collected from Ranchan Recreational Park and UNIMAS Lake at Universiti Malaysia Sarawak, Kota Samarahan, respectively. Water physicochemical parameters were also recorded. All samples were concentrated by the iron sulfate flocculation method followed by the sucrose floatation technique. Cryptosporidium and Cyclospora were detected by modified Ziehl-Neelsen technique. Correlation of the parasites distribution with water physicochemical parameters was analysed using bivariate Pearson correlation. Based on the 24 total samples of environmental water abstracted by drinking water treatment plants, all the samples (24/24; 100%) were positive with Cryptosporidium, and only 2 samples (2/24; 8.33%) were positive with Cyclospora. Based on the 12 total samples of water for recreational activities, 4 samples (4/12; 33%) were positive with Cryptosporidium, while 2 samples (2/12; 17%) were positive with Cyclospora. Cryptosporidium oocysts were negatively correlated with dissolved oxygen (DO).